Correlation of renal pathological changes with survival and prognosis in patients with diabetic nephropathy - TAN Xiao-yan; DING Guo-hua; YANG Ding-ping; YANG Hong-xia (Linchuang shenzangbing zazhi)
Objective To study and analyze the renal pathological features and prognosis of diabetic nephropathy, and to provide evidence for clinical treatment. Methods A total of 73 patients with complete follow-up information, diagnosed with diabetic nephropathy by means of renal puncture biopsy during hospitalization in Renmin Hospital of Wuhan University from January 2015 to January 2017 were analyzed retrospectively. All patients received symptomatic supportive treatment. The pathological analysis scores and prognostic effects of 73 patients with diabetic nephropathy were analyzed to evaluate whether tubulointerstitial lesions could predict the occurrence of renal endpoint events in patients with diabetic nephropathy. Results By grading according to the tubulointerstitial pathological criteria recommended by International Society of Renal Pathology in 2010, among 73 cases of DN,39 cases belonged to mild tubulointerstitial pathology group 20 cases to moderate tubulointerstitial pathology group, and 14 cases to severe tubulointerstitial pathology group. Renal tubulointerstitialcould predict the prognosis of DN patients. Further analysis showed that hemoglobin and urea nitrogen could evaluate tubulointerstitial lesions. Conclusions Renal tubulointerstitial lesions can be used as a predictor of prognosis in patients with DN. Urea nitrogen and hemoglobin can be used as clinical marker for evaluating tubulointerstitial injury, providing a new method for the treatment and prognosis of patients with DN.